KAJIAN MORFOLOGIS VERBA PANCAINDRA DALAM BAHASA MELAYU DIALEK SAMBAS - Letycia Letycia; Patriantoro Patriantoro; Agus Syahrani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study was the morphological study of verbal five senses in Sambas dialect Malayan languages in Pemangkat Sub District in Sambas Regency. The morphological study of verbal five senses that cover the kind of verbal five senses, the meaning of verbal five senses, the process of morfology which was taken by verbal of five senses, and the text suplement form on learning the curriculum 2013 Indonesian Languages. The method that was used in this research was descriptive method with the qualitative research form. The technique that was used in this research was tapping technique, interesting technique and documentary technical study whereas. The tool which was used was question list, documentation and “Tullah” film. Based on the result of analysis consist of two kinds of verbal five senses namely based on the form and based on sub-categorization. The meaning of verbal five senses analized using the lexical meaning form verbal basic five senses. The process of morfology that was used was affixation and the giving of affix meaning that attached on verbal five senses. The research data that was implied as the tool of learning Indonesian Languages at school on the curriculum 2013 the seventh grade with description text model.  Keywords: Sambas dialect Malayan language, text material suplemen, the process of morfology, verbal five senses